Toward in silico CMC: An industrial collaborative approach to model‐based process development. Issue 12 (29th August 2020) - Roush, David; Asthagiri, Dilip; Babi, Deenesh K.; Benner, Steve; Bilodeau, Camille; Carta, Giorgio; Ernst, Philipp; Fedesco, Mark; Fitzgibbon, Sean; Flamm, Matthew; Griesbach, Jan; Grosskopf, Tobias; et al.
Abstract: The Third Modeling Workshop focusing on bioprocess modeling was held in Kenilworth, NJ in May 2019. A summary of these Workshop proceedings is captured in this manuscript. Modeling is an active area of research within the biotechnology community, and there is a critical need to assess the current state and opportunities for continued investment to realize the full potential of models, including resource and time savings. Beyond individual presentations and topics of novel interest, a substantial portion of the Workshop was devoted toward group discussions of current states and future directions in modeling fields. All scales of modeling, from biophysical models at the molecular level and up through large scale facility and plant modeling, were considered in these discussions and are summarized in the manuscript. Model life cycle management from model development to implementation and sustainment are also considered for different stages of clinical development and commercial production. The manuscript provides a comprehensive overview of bioprocess modeling while suggesting an ideal future state with standardized approaches aligned across the industry. Abstract : This review covers multiple types and scales of modeling used in the bioprocessing industry from biophysical models at the molecular level and up through large scale facility and plant modeling. The current state of bioprocess modeling is assessed, and an idealized future state is proposed.